Analysis of cloudlet completion time during attack on smart grid cloud. (2015) - Mehmi, Sandeep; Verma, Harsh Kumar; Sangal, Amrit Lal
The exceptional advantages of cloud have attracted the organisations to shift their IT business on to cloud. Smart grid is maximum optimisation of energy management achieved through transmission and distribution automation and integration of smart devices. The monitoring sensors generate enormous uncorrelated data that need scalable storage servers and this requirement can be fulfilled by smart grid cloud. But the biggest concerns of organisations moving towards cloud computing are security and privacy. Precise intrusion detection techniques in addition to intrusion prevention techniques are necessary to augment cloud security. In this paper the cloudlet completion time analysis has been done under normal and attack conditions with respect to number of cloudlets, cloudlet length, virtual machine (VM) RAM and VM bandwidth in a space shared mapping policy for VM and cloudlets. The results indicate that during attack the cloudlet completion time increased drastically and this analysis can prove to be an important parameter to detect intrusion.